Konstruksi Penatalayanan Alam Suku Dayak Simpakng Kalimantan Barat - Kaseke, Fanny Y.M (SCRIPTA: Jurnal Teologi dan Pelayanan Kontekstual, 2025)
This article discusses the concept of environmental management within the context of Christian ecotheology as applied by the Dayak Simpakng community in West Kalimantan. The background of this research is rooted in the increasingly urgent environmental crisis, where indigenous communities play a vital role in conservation efforts. The methodology used in this study is a qualitative approach, with data collected through interviews and direct observations of the natural resource management practices by the Dayak Simpakng people. The findings indicate that this community applies principles of local wisdom in sustainable resource management, viewing nature as a partner in life rather than an object of exploitation. They have a clear categorization system for managing forests and land, and they perform rituals that reflect their respect for the environment.